Interview with Antonio Carlos Robert Moraes - Scarim, Paulo Cesar (Geografares, 2026)
Interview with the Brazilian geographer and professor Antonio Carlos Robert Moraes (Tônico), conducted on September 2, 2000 by Paulo Cesar Scarim, and which is part of his master’s thesis, defended at University of São Paulo (USP) in 2000, under the guidance of Professor Ani Fani Alessandri Carlos. This interview is unpublished and has never been released before.